Cyber racism : white supremacy online and the new attack on civil rights - Daniels, Jessie, 1961- (Perspectives on a multiracial America series., 2009)
In this exploration of the way racism is translated from the print-only era to the cyber era the author takes the reader through a devastatingly informative tour of white supremacy online. The book examines how white supremacist organizations have translated their printed publications onto the Internet. Included are examples of open as well as "cloaked" sites which disguise white supremacy sources as legitimate civil rights websites. Interviews with a small sample of teenagers as they surf the web, show how they encounter cloaked sites and attempt to make sense of them, mostly unsuccessfully